2020
DOI: 10.1017/s0950268820002095
|View full text |Cite
|
Sign up to set email alerts
|

Underreporting COVID-19: the curious case of the Indian subcontinent

Abstract: COVID-19 has spread across the globe with higher burden placed in Europe and North America. However, the rate of transmission has recently picked up in low- and middle-income countries, particularly in the Indian subcontinent. There is a severe underreporting bias in the existing data available from these countries mostly due to the limitation of resources and accessibility. Most studies comparing cross-country cases or fatalities could fail to account for this systematic bias and reach erroneous conclusions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 9 publications
0
37
0
Order By: Relevance
“…However, studies showed there concern about probable under reporting bias in the COVID-19 data of Bangladesh due to resource constraints ( 72 ). Self-reported syndromic data also suggests an earlier spread of the outbreak in Bangladesh ( 73 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, studies showed there concern about probable under reporting bias in the COVID-19 data of Bangladesh due to resource constraints ( 72 ). Self-reported syndromic data also suggests an earlier spread of the outbreak in Bangladesh ( 73 ).…”
Section: Resultsmentioning
confidence: 99%
“…The reason is that during an epidemic, crude CFR estimation becomes an underestimate of the actual CFR [ 5 ]. However, there are unreported cases because of both limited tests and asymptomatic or mild patients [ [40] , [41] , [42] , [43] ]. Therefore, after further adjustment for reporting rates lower than 50%, estimated CFRs became less than one-third compared to crude CFR, and survival interval adjusted CFR.…”
Section: Discussionmentioning
confidence: 99%
“…The reason is that during an epidemic crude CFR estimation becomes an underestimate of the actual CFR [5]. However, because of both limited numbers of test and presence of asymptotic or mild cases, there exists unreported cases [25][26][27][28]. Therefore, after further adjustment for reporting rates lower than 50%, estimated CFRs became less than one-third compared to crude CFR, and survival interval adjusted CFR.…”
Section: Discussionmentioning
confidence: 99%